Application of the integrated behavioral model to identify the predictors of toothbrushing practices among primary school children at Bahir Dar city, Ethiopia - Natnael Kebede; Habtamu Wondiye; Lidiya Melkamu; Tadele Fentabil Anagaw; Elias Assefa; Eyob Ketema Bogale; Gebremedhin Hailu; Yirgalem Mohammed; Bezawit Adane (BMC, 2022)
Abstract Knowing the level of behavioral intention and tooth-brushing practices is crucial for the implementation of the intervention. However, such studies are too limited in Ethiopia. The current study employed a health behavior model to identify predictors that can serve to support primary school children's attitudes, intentions, knowledge, environmental constraints, and practices of tooth brushing. Thus, this study aimed to assess tooth brushing practices and their predictors among primary school children in Bahir Dar city, Ethiopia. An Institutional based cross-sectional study was conducted among primary school children in Bahir Dar city. A multi-stage sampling technique was used to select 610 participants. Data were collected using pre-tested interviewer-administered questionnaires. Questionnaires adapted from items' previous literature were used for integrated behavioral model constructs incorporated with elicitation study results. Data were entered into Epi data and then analyzed by Stata. Descriptive statistics were done. Confirmatory factor analysis was performed to check the convergent validity of the measurement. The Internal reliability of the items was also checked using composite reliability. Multivariable logistic regression was used to predict the role of independent variables in toothbrushing practices. Moreover, path analysis was performed to check the causal effect of integrated behavioral model constructs on toothbrushing practices. The goodness of fit of the final model was checked using the Hosmer and Lemeshow test of best fit with a large p value = 0.97 and Area under receiver operating characteristics curve = 0.98. The overall prevalence of the current practice of toothbrushing among the respondents was 45.4%. The prevalence of brushing frequency was 243 (89.01%), 27 (9.89%), and 3 (1.09%) brushed once a day, twice a day, and more than twice a day respectively. Female child's [AOR 3.23, 95% CI 1.48-7.02], mothers' education [AOR 4.6; 95% CI 1.22-17.44], past experience of toothbrushing [AOR 0.042; CI 0.018-0.101], knowledge about tooth brushing practices [AOR 1.3; 95% CI 1.09-1.60], behavioral intention [AOR 2.01; 95% CI 1.74-2.32], experiential attitude [AOR 1.09; 95% CI 1.01-1.17],instrumental attitude [AOR 1.02; 95% CI 1.01-1.03], and descriptive norm [AOR 1.07; 95% CI 1.01-1.14] were predictors of toothbrushing practices. The findings indicate that the practice of toothbrushing practices among primary school students was low. Sex, mother's education, knowledge, intention, experience, experiential attitude, instrumental attitude, and descriptive norm, have significant effects on toothbrushing practices; indicating that the integrated behavioral model showed adequate utility in predicting toothbrushing practices in the study area. School-based toothbrushing practices change interventions such as communication strategy.